2022
DOI: 10.5713/ab.21.0110
|View full text |Cite
|
Sign up to set email alerts
|

Moderate dietary boron supplementation improved growth performance, crude protein digestibility and diarrhea index in weaner pigs regardless of the sanitary condition

Abstract: Moderate dietary boron supplementation improved growth performance, crude protein digestibility and diarrhea index in weaner pigs regardless to the sanitary condition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…In another study on the addition of different levels of boric acid (0, 100, 200, and 400 mg/L) to the drinking water of broiler chickens, it was determined that body weight gain was negatively affected in groups that received > 100 mg/L of boric acid [35]. It has been reported that the effects of boron on the feed conversion ratio vary in goats [36], broilers [17], laying hens [37], quails [38], pigs [39], and fish [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…In another study on the addition of different levels of boric acid (0, 100, 200, and 400 mg/L) to the drinking water of broiler chickens, it was determined that body weight gain was negatively affected in groups that received > 100 mg/L of boric acid [35]. It has been reported that the effects of boron on the feed conversion ratio vary in goats [36], broilers [17], laying hens [37], quails [38], pigs [39], and fish [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…One such effect is the prevalence of infections and diarrheal diseases leading to wasting or acute malnutrition. A piglet study has revealed that boron supplementation not only affects feed intake and protein digestion, but also improves the diarrhoea index 9 . Although the veterinary industry has long recognized boron's importance in animal nutrition, and its association with other minerals and vitamins in poultry and piggery, the combined role of boron and Vit-D in human anthropometry has received less attention.…”
Section: Boron and Its Impact On Anthropometry (Boron As A Vitamin-d ...mentioning
confidence: 99%
“…( k ) Moderate supplementation with dietary B improved growth performance, the digestibility of crude protein, and the diarrhea index in weaned pigs, regardless of health status [ 79 ].…”
Section: New Insights Into the Essentiality Of B Species In Symbiosis...mentioning
confidence: 99%